Catalytic neutralization of acidic crude oil utilizing 2-methylimidazole in polyethylene glycol with the aid of Ca/Al2O3 catalyst / Noraini Safar Che Harun - Che Harun, Noraini Safar (2019)
The Naphthenic Acid (NA) found in the acidic crude oil can leads to corrosion problem in oil refinery equipment and reduces the performances of the oil. Various methods can be used to reduce the NAs concentration such as dilution, catalytic decarboxylation and caustic washing but all these methods have its own weakness. In this study, catalytic neutralization reaction was done in order to lowering the Total Acid Number (TAN) in crude oil to below than one mg KOH/g utilizing 2-Methylimidazole in Polyethylene Glycol (PEG400) with aid of Ca/Al2O3 catalyst. The catalyst were supported on the alumina through Incipient Wetness Impregnation (IWI) methods and calcined at calcination temperatures of 800, 900 and 1000oC. The potential catalyst was characterized by using Fourier Transform Infrared Spectroscopy (FTIR), Thermogravimetry Analysis (TGA), X-ray Diffraction Spectroscopy (XRD), and Brunauer-Emmett-Teller (BET) for its physical and chemical characteristics. The result showed that Ca/Al2O3 catalyst successfully reduced to 0.52 mg KOH/g from original TAN value 4.22 mg KOH/g by using a catalyst with calcination temperature 1000oC, 0.39% (7 beads) of catalyst loading and 1000 ppm of 2-Methylimidazole in PEG. The FTIR results showed that the C-H stretching of catalyst after reaction might come from alkane and alkene group of long chain acids which has bounded to the catalyst surface around 2321.25 cm-1. For TGA results, the total weight loss of the Ca/Al2O3 32.6% due to complete removal of the impurities and water in the catalyst. For XRD showed, CaAl4O7 species was identified as the active sites for the catalyst calcined at 1000oC. BET analysis showed the Ca/Al2O3 catalyst calcined at 800oC gave the highest surface area of 120.03 m2/g compared to the catalyst calcined at 900oC and 1000oC that allows more molecular NAs to enter pores of the catalyst. In conclusion, a catalytic neutralization method was efficient in reducing NA from acidic crude oil thus the TAN value was successfully reduced to below than 1 mg KOH/g.